UPAYA ANTISIPASI PENCEGAHAN PAHAM ANTI PANCASILA MASUK SEKOLAH - Fatimah Asyari (Universitas 17 Agustus 1945 Samarinda, 2018)
This research is willing to research about how to prevent the anti -Pancasia enter the school of Indonesia especially in Balikpapan.Pancasila as the way of life for the people in Indonesia in any cases has tobe defended forever. Pancasila is absolutely existed forever in Indonesia.The research is hold in Balikpapan for one month. The method isqualitative by taking the bews frm the local daily news paper andobservtion the society among the different people of their religions, socialstatus, skin, language, originality, richness, rank, heritage and educationlevels.The conclusion of this study is : (1) Understanding the four pillarsof the life of the nation and state is very important. Therefore we mustpractice it, including the four pillars of national and state life, namelyPancasila, the 1945 Constitution, the Unitary Republic of Indonesia, andBhinneka Tunggal Ika; (2) All parties continue to maintain unity andunity in diversity;(3) Foster cooperation and tolerance with eachother;(4)Giving direction to anyone who has symptoms and anti-Pancasila;and (5)Continuous supervision at school